2007
DOI: 10.1128/jvi.00303-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structural Analysis of Novel Mutations in Human Immunodeficiency Virus Type 1 Reverse Transcriptase Involved in the Regulation of Resistance to Nonnucleoside Inhibitors

Abstract: Resistance to antivirals is a complex and dynamic phenomenon that involves more mutations than are currently known. Here, we characterize 10 additional mutations (L74V, K101Q, I135M/T, V179I, H221Y, K223E/Q, and L228H/R) in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase which are involved in the regulation of resistance to nonnucleoside reverse transcriptase inhibitors (NNRTIs). These mutations are strongly associated with NNRTI failure and strongly correlate with the classical NNRTI resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 52 publications
4
61
3
Order By: Relevance
“…We could not confirm some other previously reported interactions. Ceccherini-Silberstein et al (2007) reported a synergistic interaction between polymorphism 135T and mutation 103N for efavirenz resistance; however, in our analysis, 135T is linked to 60I. Mutation 60I has been found in patients treated with AZT (Shafer et al, 1995).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…We could not confirm some other previously reported interactions. Ceccherini-Silberstein et al (2007) reported a synergistic interaction between polymorphism 135T and mutation 103N for efavirenz resistance; however, in our analysis, 135T is linked to 60I. Mutation 60I has been found in patients treated with AZT (Shafer et al, 1995).…”
Section: Discussioncontrasting
confidence: 47%
“…Mutations at position 228 have been linked to NRTI treatment (Deforche et al, 2008a;Gonzales et al, 2003;Rhee et al, 2005;Shahriar et al, 2009). Others have suggested a role in NNRTI resistance for mutations at this position (Ceccherini-Silberstein et al, 2007;Saracino et al, 2006). However, Saracino et al (2006) did not differentiate between mutations 228H and 228R, and their univariate analysis of the impact on susceptibility cannot exclude influences from other mutations present, whilst the study of Ceccherini-Silberstein et al (2007) only provides weak evidence for mutation 228H and rather suggests an involvement in NRTI resistance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…26,27 This finding raises a possibility of differential selection process that leads to distinct drug-resistant variants under treatment because some of these mutations have been included as a candidate for positive reproductive fitness 28 and drug resistance. 8,29,30 The limitation of the current study is the smaller sample size, and the history on HIV seroconversion for the study population is unknown and hence the absence of genetic diversity between the compartments could not be related to the stage of HIV infection. In conclusion, in the present analysis, phylogenetic and mutational analysis of RT in plasma and genital secretions of HIV-1-infected ART-naive females demonstrated limited variation likely reflecting the absence of differential selection pressure and genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Because the envelope gene is a major determinant of cell tropism, 4,5 sequencing has been usually performed on this region, leaving other potentially important genes unexplored such as RT, that is primarily targeted by the cellular immune response and may also significantly impact viral quasi-species evolution and therefore drug resistance. [6][7][8] The purpose of this study is to ascertain whether RT is subjected to diverse selection pressure in plasma and genital secretions of antiretroviral treatment (ART)-naive females, which is critical to the development of an effective drug regimen against those variants residing in genital compartments.…”
Section: Introductionmentioning
confidence: 99%